2016
DOI: 10.18632/oncotarget.13814
|View full text |Cite
|
Sign up to set email alerts
|

The bromodomain inhibitor OTX015 (MK-8628) exerts anti-tumor activity in triple-negative breast cancer models as single agent and in combination with everolimus

Abstract: Triple-negative breast cancer (TNBC) is an aggressive and heterogeneous subgroup of breast tumors clinically defined by the lack of estrogen, progesterone and HER2 receptors, limiting the use of the targeted therapies employed in other breast malignancies. Recent evidence indicates that c-MYC is a key driver of TNBC. The BET-bromodomain inhibitor OTX015 (MK-8628) has potent antiproliferative activity accompanied by c-MYC down-regulation in several tumor types, and has demonstrated synergism with the mTOR inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 48 publications
1
76
0
Order By: Relevance
“…A novel and promising approach is based on the use of compounds able to target the epigenome of breast cancer cells. In particular, among the molecules that inhibit the transcription of growth-promoting genes by acting on the "readers" of the acetylated histone marks, the bromo-and extra-terminal domain (BET) inhibitor JQ1 ((S)-tertbutyl2-(4-(4-chlorophenyl)-2,3,9-trimethyl-6H-thieno(3,2-f) (1,2,4)triazolo(4,3-a) (1,4)diazepin-6-yl)acetate) has shown a strong anti-proliferative action against TNBC cell lines and xenografts [4][5][6][7]. JQ1 acts by competing with acetylated histone residues, thus removing BET proteins from their chromatin targets.…”
Section: Introductionmentioning
confidence: 99%
“…A novel and promising approach is based on the use of compounds able to target the epigenome of breast cancer cells. In particular, among the molecules that inhibit the transcription of growth-promoting genes by acting on the "readers" of the acetylated histone marks, the bromo-and extra-terminal domain (BET) inhibitor JQ1 ((S)-tertbutyl2-(4-(4-chlorophenyl)-2,3,9-trimethyl-6H-thieno(3,2-f) (1,2,4)triazolo(4,3-a) (1,4)diazepin-6-yl)acetate) has shown a strong anti-proliferative action against TNBC cell lines and xenografts [4][5][6][7]. JQ1 acts by competing with acetylated histone residues, thus removing BET proteins from their chromatin targets.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, selectivity and potency of tool compounds are often insufficient resulting in contradictory and erroneous results 1922 . Following the disclosure of potent BET BRD inhibitors, other members of the BRD-family of interaction modules have been found to be highly druggable 23 , resulting in the identification of chemical fragments that were subsequently developed into potent and selective chemical probes 2431 . However, BRDs outside the BET family have not been found to be major regulators of primary transcription control, posing challenges for the discovery of functional roles of these conserved domains 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Bromodomains are an attractive target for cancer therapeutics and have been intensively studied as treatment in many cancer types (47). Several studies reported the antiproliferative effects of bromodomain inhibitors in breast cancer cell lines and a reduction of tumor mass in mouse xenograft models (48)(49)(50). Arrested tumor growth by bromodomain inhibitors has also been shown in preclinical models of lung cancer.…”
Section: Discussionmentioning
confidence: 99%